ANALYSIS OF THE INCOME OF BEEF IN THE CIUDAD DEL ESTE MARKET - Fernanda Vargas Britez, Angela; Belén Silvero Rojas , Natalia; de Jesús Esquivel Núñez , Anderson (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this paper is to analyze the consequences of the entry of beef through the triple border for distributors and merchants of the national product in the Ciudad del Este market. The bibliographic review carried out by the authors addresses three thematic units that revolve around concepts related to the market, the beef market, meat marketing, the irregular entry of beef in Ciudad del Este and the legal provisions that make up the legal framework that regulates this economic activity. The research has a mixed approach, which qualitatively and quantitatively analyzes the data obtained from the study sample. The descriptive research level. Likewise, it is concluded that the entry of beef through the triple border has severe consequences for distributors and merchants of meat products in the Ciudad del Este market.